Classical Chinese poetry in Singapore : witnesses to social and cultural transformations in the Chinese community - Wang, Bing, 1979- (Lexington Books, 2018)
This book examines classical Chinese poetry in Singapore from a sociocultural perspective. It is suitable for the readers in Chinese studies, Asian studies, and cultural studies.